Dekonstruksi Asas Kepastian Hukum dalam Regulasi Ketenagakerjaan Indonesia - Deki Satriawan; Hery Kurniawan Zaenal; Achmad Nur Wachid; Yudhistira Prawira Utama; Marco Orias (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This article examines the deconstruction of legal certainty within Indonesian labor regulation by situating it in contemporary political–legal transformations. Using systematic library research, the study synthesizes doctrinal analyses, constitutional debates, and critical legal scholarship on omnibus legislation, employment relations, and regulatory governance. The findings demonstrate that legal certainty has progressively shifted from a substantive principle protecting workers’ rights toward an instrumental and procedural construct serving regulatory flexibility, economic competitiveness, and administrative efficiency. This transformation produces normative fragmentation, weakens coherent protection standards, and generates interpretive asymmetries between legislation, implementing regulations, and judicial practices. By integrating deconstructive legal theory with labor law analysis, the article reveals how legal certainty operates as a contingent discourse rather than a fixed normative guarantee. The study contributes theoretically by reframing legal certainty as a dynamic and contested concept, and methodologically by offering a replicable synthesis model for critical normative research